Maritime Applications of Adhesively-Bonded Joints - João C.M. Santos; Raul D.S.G. Campilho (Current Approaches in Engineering Research and Technology Vol. 4, 2024)
Canoeing, a nautical sport with a history spanning thousands of years, originated as a means of survival. Over time, the focus shifted towards utilizing composite materials and adhesive bonding in boat construction to enhance quality and performance. In this study, an adhesive joint within a canoeing vessel, specifically the connection between the hull and deck of a kayak, is analysed using cohesive zone modelling (CZM). The objective is to assess the efficacy of various joint configurations, explore geometric alterations, and evaluate different adhesive types. The process begins with the validation of CZM to ensure its reliability for subsequent analyses. Through a series of numerical simulations, the existing joint configuration is evaluated, geometric modifications are explored, and the suitability of diverse adhesive options is considered. Ultimately, the optimal geometry-adhesive combination is identified, showing a marked enhancement over the current joint utilized in canoeing boats, up to 183.8% for the bending load.